Existing seasonal flexibility in US manufacturing energy use. (2nd June 2021) - Lydon, John J; Ciez, Rebecca E
Abstract: Renewable electricity will likely play a substantial role in a decarbonized energy system, and there are well-known seasonal patterns to renewable electricity output. We can manage these seasonal fluctuations by overbuilding our electricity generation capacity, implementing seasonal storage, or managing our energy demands seasonally. If industrial processes are more integrated with the broader energy system, they could play a role in managing these seasonal patterns, as they do not directly serve life-sustaining energy demands, and their products may be stored and sold at a later date. Here, we combine GDP, manufacturing, and energy consumption data to look at how existing manufacturing facilities operate, focusing on the utilization of their operating capacity and how utilization correlates with state-level energy consumption. Of the 12 states with the largest manufacturing energy demand, we find that they use an average of 75%–81% of operating capacity between 2014–2018. In most of these states, there is a positive relationship between energy consumption and capacity utilization, and decreasing 10% of manufacturing capacity utilization could translate into energy savings that are relatively large when compared to electricity sales for the same time period, implying that seasonal ramping of industrial production could play a substantial role in adjusting to seasonal energy trends.